Estimated Energy Consumption Of Electricity At APJ Cilacap In 2011-2016 Using Leap Software - Pradana, AP Hendra; Windarto, Joko; Winardi, Bambang (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Electrical system in the Central Java Province is managed by PT PLN (Persero). The Electrical energy distribution is carried by the APJ (Service Area Network). One of APJ operating in the Central Java Province is APJ Cilacap, APJ Cilacap which is responsible to fulfill the electricity needs in the District of Cilacap and Kebumen. It makes APJ Cilacap as manager of the utility company should be able to provide the energy needs of electricity in both area. In addition of electrical energy demand’s problem, the problems belong to SAIDI, SAIFI and line losses also becomes a problem of electrical energy distribution. Therefore, it needs to have the electrical energy planning so that energy needs, SAIDI, SAIFI and line losses can be known for the following years. In Preparation of Planning estimates that the software used are LEAP (Long Range Energy Planning System) version 2008.0.0.96. In Planning Making using two scenarios namely BAU (Base As Usual) is the result of scenario planning is still the same trend with the growth of base year or there is no policy affected and RPTL PLN which is based on RUPTL PLN (General Planning of Electricity Supply) in period 2012-2016. From the results of planning using LEAP, projected electricity supply, BAU scenario growth in electrical energy consumption, has the average value of customers equal to the Household sector in UPJ Cilacap, Majenang, Sidareja, and Kroya that is 0.41% per year, while the commercial sector, Industrial, and General are 5.39%, 2.33%, 4.60% per year, while UPJ Kebumen and Kroya for each sector 0, 51%, 4.27%, 7.40%, 4.48% per year. While the projections for electricity supply, outage rate index (SAIDI SAIFI), and losses, RPTL PLN scenario of electricity energy consumption growth follows a policy document RUPTL PLN year 2009-2019. Policy scenarios in RPTL PLN where the electrical energy consumption projections estimates the population growth of 0.3% per year, PDRB growth of 4.5% -5.83% per year, Electrification Ratio in 2019 is targeted at 97.5%, and 4.99% growth in connected power per year. For Policy in making electric energy losses in 2019 is targeted at 5.65%. While in making target of outage Index (SAIDI SAIFI) predicted value of SAIDI in the year 2019 at 77,44 minute/consument/years and the value of SAIFI in 2019 by 4,4 times /consument/years. Keyword : Electricity, SAIDI SAIFI, Energy losses, Planning, LEAP